Water-soluble multimode fluorescent thermometers based on porphyrins photosensitizers. (May 2021) - Kolesnikov, Ilya E.; Kurochkin, Mikhail A.; Meshkov, Ivan N.; Akasov, Roman A.; Kalinichev, Alexey A.; Kolesnikov, Evgenii Yu.; Gorbunova, Yulia G.; Lähderanta, Erkki
Abstract: Anti-cancer treatment efficiency can be significantly enhanced by the synergistic effect of the combined phototherapy that nowadays is under intensive preclinical and clinical studies. To minimize collateral damage, the combined phototherapy should be accompanied by a real-time thermal sensing. However, it is still challenging to develop multifunctional agent which combines therapy and temperature control. In the present study, contactless fluorescent thermometry based on ratiometric and lifetime approaches was realized using water-soluble anionic meso- tetrasulfonatophenylporphyrinate (tetra sodium salt) TSPH2 and cationic meso -mono(4-pyridyl)-triphenylporphyrinato)phosphorus(V) bromide MPyPP(OH)2 porphyrins photosensitizers. Both sensing techniques provide simple linear calibration curves in the biological temperature range. Thermometric performance of the suggested porphyrins was evaluated in terms of relative sensitivity, temperature resolution and repeatability and was found to be in upper range among porphyrin-based thermometers reaching 1% K −1 and 0.1 °C. The relative sensitivity was enhanced from 2 to 7 times by using peak-to-valley ratio compared to usual peak-to-peak ratio. Porphyrins' cytotoxicity was studied in vitro both in dark and blue-light activated conditions. Exposure-dependent cell viability showed that porphyrins could be used as molecular thermometers for phototherapy to avoid heat-induced adverse effects or as promising photosensitizers depending on chosen laser power. Graphical abstract: Unlabelled Image Highlights: Water-soluble anionic and cationic porphyrins were firstly demonstrated as fluorescence thermometers. Thermal sensing was realized via ratiometric and lifetime-based approaches. Ratiometric relative thermal sensitivity was enhanced from 2 to 7 times by appropriate choice of emission lines. Porphyrins' cytotoxicity was studied in vitro both in dark and blue-light activated conditions.